2022
DOI: 10.5501/wjv.v11.i6.453
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic manifestations of coronavirus disease 2019 infection: Clinical and laboratory perspective

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2, has become a global challenge of unprecedented nature since December 2019. Although most patients with COVID-19 exhibit mild clinical manifestations and upper respiratory tract involvement, in approximately 5%-10% of patients, the disease is severe and involves multiple organs, leading to multi-organ dysfunction and failure. The liver and gastrointestinal tract are also frequently involved in COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In addition, our study found a lower reported prevalence of liver disease as an associated comorbidity at admission (2.1%), whereas Karadeniz et al [25] did not report any such prevalence in their cohort. Several pathways have been proposed in the pathogenesis of liver injury in patients with COVID-19, including the cytopathic effect of the virus, cytokine storm, systemic inflammatory response syndrome, thrombosis, hypoxia and sepsis [38]. In addition, hepatocytes and cholangiocytes express angiotensin-converting enzyme receptor 2 during long COVID-19, thereby incurring a mild derangement of hepatic biomarkers that sometimes result in the development of a cholangiopathy [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study found a lower reported prevalence of liver disease as an associated comorbidity at admission (2.1%), whereas Karadeniz et al [25] did not report any such prevalence in their cohort. Several pathways have been proposed in the pathogenesis of liver injury in patients with COVID-19, including the cytopathic effect of the virus, cytokine storm, systemic inflammatory response syndrome, thrombosis, hypoxia and sepsis [38]. In addition, hepatocytes and cholangiocytes express angiotensin-converting enzyme receptor 2 during long COVID-19, thereby incurring a mild derangement of hepatic biomarkers that sometimes result in the development of a cholangiopathy [39].…”
Section: Discussionmentioning
confidence: 99%
“…The liver has been described as the second organ after the lungs to be involved in the course of the disease, resulting in hepatobiliary complications among up to 29% of patients [24][25][26][27]. Chen et al found patients infected with coronavirus and coexisting abnormalities in liver tests to present a greater risk of systemic inflammatory response syndrome (SIRS) and higher overall mortality rates [28].…”
Section: Hepatic Face Of Novel Coronavirus Infectionmentioning
confidence: 99%
“…The exact mechanism underlying liver injury in the context of COVID‐19 infection remains not fully elucidated. However, several hypotheses have been suggested, encompassing the direct impact of the virus on cells, immune system dysfunction, systemic inflammatory response syndrome, cytokine storm, sepsis, vascular clotting, hypoxia, and ischemia–reperfusion injury 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…However, several hypotheses have been suggested, encompassing the direct impact of the virus on cells, immune system dysfunction, systemic inflammatory response syndrome, cytokine storm, sepsis, vascular clotting, hypoxia, and ischemia-reperfusion injury. 5,6 We present a case of a 4-year-old girl with thalassemia minor who presented with fever, jaundice, and elevated liver enzymes. Despite initial suspicion of acute viral hepatitis and treatment initiation, further investigations revealed significantly elevated SARS-CoV-2 antibodies, highlighting a rare presentation of COVID-19-associated liver injury.…”
mentioning
confidence: 99%